Measuring farmer conservation behaviors: Challenges and best practices. (January 2018) - Floress, Kristin; Reimer, Adam; Thompson, Aaron; Burbach, Mark; Knutson, Cody; Prokopy, Linda; Ribaudo, Marc; Ulrich-Schad, Jessica
Highlights: Agricultural production practices can significantly impact environmental quality. A framework for effectively measuring farmers' conservation behaviors is developed. Framework includes purposes of willingness/intent and actual behavior measures. Three purposes identified: project level, policy development, theory testing. Best practices for measuring conservation behavior are provided. Abstract: This article presents a guide for understanding the purposes and appropriate uses of different measures of conservation behavior. While applicable across natural resource management contexts, we primarily draw upon agricultural conservation research to illustrate our points. Farmers are often of interest to researchers, program managers, extension professionals, and non-governmental environmental organizations due to the significant impact of agricultural production practices on environmental resources. Practitioners are often interested in producer behaviors when they are planning or evaluating a project, developing or evaluating policy, or developing and testing theory. Within those bounds, we identify when it is most useful to assess an actual behavior (self-reported or observed) or behavioral intention (willingness or intent to pay/accept, support/participate in a policy or program, or engage in a conservation practice), and present examples of how they have been used in the past. We close with three recommendations for those conducting research related to agricultural producer behaviors: 1) research should be theoretically grounded, even when the purpose isn't to develop theory; 2) great care should be used when selecting behavior measures, dependent upon the purpose of the research, and 3) composite measures should be used when possible and appropriate.